Tricks and pitfalls in the surgical treatment of malignant bone tumours of the forearm in children and adolescents - EROL, BÜLENT (BRITISH EDITORIAL SOC BONE & JOINT SURGERY, 2021)
Malignant bone tumours around the forearm are rare. Nowadays, oncological and surgical management of bone sarcomas of this region has improved significantly. Although the anatomical features are complex, limb-sparing surgery is possible with wide surgical resection. Biological reconstruction methods are promising in this anatomically unique region. In addition, meticulous soft-tissue reconstruction yields good functional results in the hand and wrist. This study reviews malignant bone tumours of the forearm and their oncological and surgical management. Malignant bone tumours should be treated with a multidisciplinary approach based on chemotherapy, radiotherapy and limb salvage procedures.
Keywords: bone tumours; forearm; children; sarcomas; LIMB-SALVAGE SURGERY; ONCOLOGICAL OUTCOMES; HAND; OSTEOSARCOMA; SARCOMAS; RECONSTRUCTION; CHONDROSARCOMA; WRIST